Petascale high order dynamic rupture earthquake simulations on heterogeneous supercomputers - Heinecke, Alexander; Breuer, Alexander; Rettenberger, Sebastian; Bader, Michael; Gabriel, Alice-Agnes; Pelties, Christian; Bode, Arndt; Barth, William; Liao, Xiang-Ke; Vaidyanathan, Karthikeyan; Smelyanskiy, Mikhail; Dubey, Pradeep (Proceedings of the International Conference for High Performance Computing, Networking, Storage and Analysis, 2014)
We present an end-to-end optimization of the innovative Arbitrary high-order DERivative Discontinuous Galerkin (ADER-DG) software SeisSol targeting Intel® Xeon Phi™ coprocessor platforms, achieving unprecedented earthquake model complexity through coupled simulation of full frictional sliding and seismic wave propagation. SeisSol exploits unstructured meshes to flexibly adapt for complicated geometries in realistic geological models. Seismic wave propagation is solved simultaneously with earthquake faulting in a multiphysical manner leading to a heterogeneous solver structure. Our architecture-aware optimizations deliver up to 50% of peak performance, and introduce an efficient compute--communication overlapping scheme shadowing the multiphysics computations. SeisSol delivers near-optimal weak scaling, reaching 8.6 DP-PFLOPS on 8,192 nodes of the Tianhe-2 supercomputer. Our performance model projects reaching 18--20 DP-PFLOPS on the full Tianhe-2 machine. Of special relevance to modern civil engineering needs, our pioneering simulation of the 1992 Landers earthquake shows highly detailed rupture evolution and ground motion at frequencies up to 10 Hz.